Study Perbandingan Analisis Kuat Tekan Beton Antara Metode Perancangan Amerika Concrete Institute Dengan Perancangan Inggris - Masta'in Masta'in (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2015)
Concrete is a construction material that is most often used, because it has many advantages both in terms of structure, economic implementation and maintenance. To determine the compressive strength of concrete using the method bias Road Note No.4, American Concrete Instiitute methods, methods of English (The British Mix Design Method) method and Try-coba.Tujuan this study was to achieve compressive strength of concrete characteristics (σ'bk = 300 kg / cm2) obtained from the method of designing the American concrete Institute (ACI) and the British design method (the British Mix Design method) by using the same material concrete apartment blocks. From research conducted in get the compressive strength of concrete produced by the method of the American Concrete Institute σ 'bk = 399.313 kg / cm2 and British methods σ' bk = 399.313 kg / cm2. The price per cubic meter of concrete with the method of the American Concrete Institute Rp. , 605 222, - and the method of British Rp. 662 759, -. Then the price per cubic meter of concrete with the method of the American Concrete Institute cheaper than the British method.